Pregled metod za določanje številčnosti prostoživečih parkljarjev - Flajšman, Katarina (Acta silvae et ligni, 2019)
The information on absolute and/or relative abundance of wild ungulates is one of the key parameters for sustainable and efficient management. Wild ungulates are the most important and abundant group of game species in Slovenia; however, there are currently no standard census methods, which would be performed on the annual basis. There are various methods for estimating wild ungulate abundance and several criteria have to be met, when selecting the most suitable one. The most important criteria that have to be taken into account are studied species, habitat characteristics, size of the studied area, population density and cost efficiency. Besides the faecal pellet group method, which has already been used in Slovenia to estimate the abundance of roe deer and red deer, a suitable method is also the kilometre index. The reliable methods for wild boar are camera traps, drive counts and distance sampling with thermovision and, for chamois, ground counts and aerial counts.
Keywords: census methods; gostota populacije; metode za ocenjevanje gostote; metode za ocenjevanje številčnosti; parkljarji; population abundance; population density; številčnost populacije; ungulates